Minicurso de introdução à astronomia instrumental com kit para smartphone e telescópio - Moreira, Heliomárzio Rodrigues (2019)
One of the gadgets most used by young people today are smartphones. In its objectives, the educational product presents the proposal of a practical mini-course of astronomy with the construction of an adapter and a spectroscope for the use with the smartphone in a telescope permeating the Maker culture, and "do it yourself”. The kit will be presented as a set of challenges for participants, who will need to do their projects with creativity, explore possibilities, and be experimenters who will learn from mistakes and hits. The cooperation work will help them to trade some ideas to develop some skills at the school ambient. The gadget’s camera with the astronomy apps associated with the technique of image taking, celestial objects identification, telescope handling and the kit, will help to register images of the stars, planets and the moon getting their related luminous specters by the telescope. The astronomy approach at the physics classes at the high school Physics classes is restricted to small stretches of optics and gravitation that are restricted to lunar and solar eclipses, or in the Laws of Kepler and Newton, depending on the school script and the school itself, without a significant contextualization for the student. While the astronomy is featured on big discoverys, those news pass far of the classroom. Meanwhile Astronomy is the subject of great breakthroughs and this news seems to go unnoticed in the classroom. From a proposal for the physics class are shown the possibilities of making images of the night sky involving observations to the telescope. Students are invited to attend a short course of four lessons with activities in the classroom and open-air, at times previously agreed with the School to involve the student with collaborative and investigative projects with challenges, assembling and application of tools that will aid in obtaining astronomical images and spectra with a smartphone. Applications, astrophotography techniques and experimental physics are used to understand the physical phenomena involved in the process of recording astronomical images. Concepts of optics, wave and astrophysics are introduced. Emphasis is given to light diffraction for image register. The evaluation is continued, occurring throughout the event, ending on a debate at the last day. The continue evaluation lasts for the whole event. There are some suggestions of activities with questions for those who want. At this form, on a more participative ambience, the registration of the stars, moon phases and planets possibility the contextualization of physics classes making them more attractive to the high school student.